If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x=(x+20)/2=3x
We move all terms to the left:
x-((x+20)/2)=0
We multiply all the terms by the denominator
x*2)-((x+20)=0
Wy multiply elements
2x^2=0
a = 2; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·2·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:$x=\frac{-b}{2a}=\frac{0}{4}=0$
| 6(x+4)=74”2 | | 10y=-7 | | 5(x+2)=7(15) | | 2r^2-r-28=0 | | 5x+2=105 | | 5/7=15/x+2 | | 2r^2-r-16=0 | | 50+2x-3x+10x+10=0 | | 5+3x-4+10+2x=0 | | 5x-3+2+3+2x=0 | | 6r^2+r+28=0 | | -6r^2-r-28=0 | | 1.6x^2-3x=0 | | 6x-2=2×+10 | | 5x*2x=90 | | 5x*2x=250 | | 5xx2x=250 | | 2x-7/8+x=2x+7/2+5 | | -8x^-38x-35=0 | | -2(2y-4)-y=-3(y-2) | | 3x-5x+7=x-4+11 | | 2.25-a+12=0 | | 7x=x2-5 | | 8-2w=-14 | | 3×+y=90×+y=50 | | x/31.24=5 | | y+36=102,y+14= | | -6v-18=-3(v+8) | | (1n÷4)+2=7 | | 3a(a+4)–2a+7= | | -2.1x+4(10.2)=5.3 | | 9(3x+2)-10×=12x-7 |